The Influences of Social Standard to Woman Psychology in Toni Morrison’s The Bluest Eye - Yanti Rahayuningsih; Rahmatul Khasanah; Ika Destina (Lembaga Pengembangan Kinerja Dosen, 2025)
The aim of this study is to analyze the influence of social standard to woman’s psychology in Toni Morisson’s the Bluest Eye. The theory which had been used is social psychology from Handerson and Clarke. The additional theory is reader response from Richard Beach. This research utilizes the qualitative research design. The primer data collected by scrutinizing the novel Toni Morisson’s the Bluest Eye and the secondary data were taken from others resources. The finding shows the relevance of the social standard which had influences the African – American little girl, the main character. Conversely, during the creation of The Bluest Eye, Toni Morrison similarly encountered the prevailing societal mindset that equates whiteness, blue eyes, harmonious family in the real world. Consequently, the worldview Morrison presents in the novel reflects historical and social conditions which affect the psychology the woman character in the novel. Morrison aims to convey the message that social standard should not be regarded as the ultimate ideal of beauty because its implication into metal wellness.